Frequency and Characteristics of Oral Malignant Lesions in an Iranian Population: A 10-year Retrospective Study - Bakhshi, Mahin; Shamloo, Nafiseh; Bayani, Mohammad Nasir; Bagheri , Leyla; Kashefi Baher, Mohammadreza (Journal of Dental School, 2026)
Objective(s): Oral malignancies pose a significant global health challenge. Oral squamous cell carcinoma (OSCC) is the most common oral cancer, yet its prevalence and clinical pattern vary by region, lifestyle, and risk factors. Despite its high burden, especially in Asia, epidemiological data remain inconsistent. This study provided updated insights on oral malignant lesions to inform early detection and optimize treatment approaches. Methods: This cross-sectional retrospective study reviewed oral cancer records at Department of Oral Medicine at Shahid Beheshti University of Medical Sciences, Tehran, Iran over the past 10 years. Demographic, clinical data, and risk factors were analyzed. Obtained data were analyzed using Fisher’s exact test with a statistical significance of P<0.05. Results: Fifty-two oral cancer cases were identified, with a mean age of 59.67 years and a male-to-female ratio of 1:1.26. The average duration of involvement was 26.87 weeks, with the most common chief complaints being swelling, ulceration, and pain, respectively. Exophytic lesions were the most frequently observed clinical manifestation (69.2%), with the tongue being the most common site of involvement. The most common type of oral cancer was OSCC accounting for 71.2% of cases. Notably, only 25% of patients had identified risk factors for oral cancer. Conclusion: The pattern of oral cancer observed in the present study was largely consistent with previous research. Oral cancer may be more prevalent among women in the absence of significant risk factors. Further exploration of cancer risk factors is essential for guiding diagnosis, treatment, and public awareness.